Predictors of societal and individual resilience across two and a half years of varied adversities - Arielle Kaim; Maya Siman Tov; Shaul Kimhi; Hadas Marciano; Yohanan Eshel; Bruria Adini (Scientific Reports)
Abstract Over the recent two and a half years, Israel has navigated significant socio-political turmoil, encompassing military conflict and war, alongside the global health emergency presented by COVID-19. This research aimed to uncover key predictors that reliably forecast the public’s ability to adapt, recover, and thrive amidst diverse challenging scenarios. It particularly focused on examining the characteristics of societal and individual resilience in the face of varied adversities such as pandemics, military confrontations, and socio-political disruptions experienced by Israeli society. Utilizing a quasi-longitudinal approach over twelve time points, the study assessed societal and individual resilience, hope, perceived threat, symptoms of distress, and demographic information which were collected at each measurement through an online panel conducted across two and a half years in Israel. Notable variations in resilience were observed corresponding to specific events. Societal resilience reached its highest level during the 2023 Israel-Hamas conflict, whereas individual resilience saw its peak in the early stages of the COVID-19 pandemic, which subsequently waned. Hope was found to be a consisten predictor of both societal and individual resilience, with distress consistently was found to have a negative association with individual resilience. The study underscores the fluidity of resilience, steered by levels of hope and distress. These insights are vital for formulating interventions to bolster resilience amid adverse conditions.